(3GdfWb Gdeaghe aj Md eTcdGJ GdOQ GdefXhes - (3eMeO Hf eMeO Hf YHO GdSdGe Hf CMeO Hf YHO Gddg Lfhf, eMeO Lfhf,J (B1326 (3g` s; (3eMeO Hf eMeO Hf YHO GdSdGe Hf CMeO Hf YHO Gddg Lfhf, eMeO Lfhf,J (B1326 (3g` s ((3YHOQHg Hf ecfhf s)
(3ChdgG (B:s
(3hHYO , agPG JbjO SejJg GdfWb Gdeaghe SHHg Gfi cfJ bjOJ QSGdI SeJgG GdOQ GdefXhe ai fUQI GdbWH GdecJhe, hPcQJ ajgG ebGdGJ ddTjN CHj GdYHGS GdJLeGfi s
(3BNQgG (B:s
(3hcGf GdaQGZ efg eJe TYHGf GdCHQc YGe (B1314 (3g`, Ydi jO YHOQHg eMeO cfhf, habg Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B431 - (3U(B444s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B77s
Keywords: (3GdJGQjNs